Interdisciplinary approach to automated negotiation: a preliminary report - Lopes, Fernando (2008)
Autonomous agents with negotiation competence are becoming increasingly important and pervasive. This paper follows an interdisciplinary approach to build autonomous negotiating agents by considering both game-theoretic techniques and bargaining procedures from the social sciences. The paper presents a generic model that handles bilateral multi-issue negotiation, describes equilibrium strategies for the bargaining game of alternating offers, and formalizes important strategies used by human negotiators. Autonomous agents equipped with the model are able to negotiate under both complete and incomplete information, thereby making them very compelling for automated negotiation.